Abilities of blood reinfusion in the surgical correction of scoliotic deformity - Khmyzov Andrеy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The surgical treatment of the scoliotic deformity entails a significant blood loss, which requires a careful selection of the infusion-transfusion therapy. The above therapy, including without any use of donor blood preparations, should take into account the available initial cardiopulmonary pathology.